Business Model Canvas PT Zakiah Dina Tayyibah: Implementasi Prinsip Syariah - Ana Karerina; Dera Dera; Wafiq Asizah; Zidny Ilman Nafia (Yayasan Literasi Sains Indonesia, 2026)
This research aims to review and describe the implementation of Sharia principles and service quality at PT Zakiah Dina Tayyibah Tours & Travel Umroh and Special Hajj, which is headquartered in Parepare City. Utilizing a descriptive qualitative method, data was collected through in-depth interviews, observation, and documentation. The focus of the study covers four aspects: management system, transaction mechanism, corporate culture, and product promotion. The research findings indicate that PT Zakiah Dina Tayyibah has implemented Sharia principles comprehensively across its entire operation. Management is based on the values of amanah (trust), honesty, professionalism, and social responsibility. The transaction mechanism employs the Ijarah al-A’mal contract (service lease), where the company acts as a service provider leasing the benefit of Umrah services to the pilgrims. Transactions are conducted transparently with valid contract evidence and are free from elements of riba (usury), gharar (uncertainty), and maisir (speculation). The corporate culture prominently highlights the values of familial relationship, amanah (trustworthiness), and worship-based service. Meanwhile, promotion is carried out ethically and honestly and is oriented towards the maslahat (benefit/welfare) of the pilgrims, such as offering promotional prices on Umrah packages (Silver, Gold, Platinum) to commemorate the company's anniversary (milad). This strategic framework is also explained through the Business Model Canvas (BMC), which shows that the company's Value Propositions center on providing pilgrimage services that comply with Sharia. The company's rapid growth indicates that the implementation of Sharia principles has successfully maintained the trust (amanah) and loyalty of the pilgrims.